Effect of female partner-led brochures method on knowledge and intention for prostate cancer screening among men in Kiambu County, Kenya - Kimani, Peterson K.; Muchiri, Joseph; Nyongesa, Margaret W. (International Journal Of Community Medicine And Public Health, 2024)
Background: Prostate cancer (PC) is a problem of public health concern globally. The problem is further complicated by the low rates of screening which results in late detection of the disease. Further, the misconception regarding PC screening (PCS) methods further makes men avoid screening. The main objective of the study was to evaluate the effect of female partner-led brochures method on knowledge and intention for PC screening among men in Kiambu County, Kenya. Methods: The research adopted a randomized controlled trial study design. Multistage sampling was employed in this study. The sample size was determined using Magnani formulae and a total of 279 respondents were recruited in the study. The Chi-square test was used to assess the difference in intention and knowledge of PC between the control and intervention groups. Further difference in difference analysis was used to assess the overall effect of the female partner-specific gain-framed and loss-framed brochures intervention on the intention of PCS and knowledge on PC. Results: The intervention groups had a significantly higher mean difference in difference in knowledge about PC than the control group with the group intervened using gain-framed and loss-framed brochures having a mean DID of 4.989 (3.561–6.418) and 5.264 (3.804–6.724) respectively. The increase in knowledge was more in the group intervened using loss-framed brochures. Conclusions: The study recommends the utilization of a combined approach of gain and loss-framed messaging in enhancing PCS.